GAGASAN PENGADUAN KONSTITUSIONAL DAN PENERAPANNYA DALAM SISTEM KETATANEGARAAN INDONESIA - Ari Asmono (Universitas Airlangga, 2011)
Constitutional complaint has an important role in a democratic state of law. constitutional complaint serves as a mechanism for the protection of citizen’s constitutional rights are violated by the authorities. with protected constitutional rights of a citizen, then a democratic state of law will be realized very well.Keywords : constitutional complaint, citizen’s constitutional rights, constitutional court.